Changes to environmental parameters that control tropical cyclone genesis under global warming. Issue 10 (23rd May 2013) - Murakami, Hiroyuki; Li, Tim; Peng, Melinda
<x xml:space="preserve">Abstract</x> [1] This study uses the Meteorological Research Institute high‐resolution Atmospheric Climate Model to determine whether environmental parameters that control tropical cyclone genesis in the Western North Pacific (WNP) and North Atlantic (NA) may differ in the global warming state. A box difference index was computed to quantitatively assess the role of environmental controlling parameters. The diagnosis of the model outputs shows that in the WNP, dynamic variables are of primary importance for separating developing and nondeveloping disturbances in the present‐day climate, and such a relationship remains unchanged in a future warmer climate. This is in contrast to the NA, where box difference index increases for all dynamic variables investigated while it shows little change for thermodynamic variables. This implies that, when compared with the present‐day climate in which thermodynamic variables have a major control on tropical cyclone genesis, dynamic and thermodynamic variables have equal control in the NA under the future warmer climate.